PENGARUH CUTTING SPEED TERHADAP PEMAKAIAN DAYA LISTRIK PADA PROSES BUBUT POROS S 45 C DENGAN MESIN KENT USA RML-1640T - Tertius Ulaan; Rudy Poeng; I Nyoman Gede; Romels Lumintang; Irvan Rondonuwu (JURNAL POROS TEKNIK MESIN UNSRAT, 2023)
In the turning that requires power to do so, there are several factors that affect the power required in tuning, cutting speed depth of cut, feeding workpiece material, and others. Of the several factors that affect the power of a lathe The purpose of this study was to analyze “the effect of cutting speed on electrical power consumption on the KENT USA RML-1640T lathe” in the mechanical engineering of Sam Ratulangi University (Unsrat). To obtain research results, it is necessary to test the lathe by varying the rotation by using a feeding motion and a fixed depth of cut and the same test abject material. The results of the analysis obtained from this study indicate that the increasing cutting speed tends to increase the use of electrical power on the lathe. From the results of simple liniear regression analysis, the regression line equation predicts that for every 1m/min increase by Rp. 0.087. From the results of the significant test, it is found that cutting speed has a significant effect on electric power consumption on the lathe Keywords: Cutting Speed, Electric power, Lathe Proses